Basal‐bolus insulin therapy reduces maternal triglycerides in gestational diabetes without modifying cholesteryl ester transfer protein activity. Issue 9 (10th July 2017) - Olmos, Pablo R.; Borzone, Gisella R.
Abstract: Aim: Macrosomia in the offspring of overweight/obese mothers with glucose‐controlled gestational diabetes mellitus (GDM) is due to excessive rise of maternal triglycerides (TG). We aimed to ascertain whether basal‐bolus insulin therapy (BBIT), or other components of the treatment, could reduce TG in GDM. Methods: We studied the records of 131 singleton pregnancies with GDM, using stepwise multiple linear regression, Mann–Whitney, χ 2, and Jonckheere–Terpstra tests. As maternal TG increased steadily during normal pregnancy, these were transformed as z ‐scores. The atherogenic index of plasma (AIP) was calculated as a measure of cholesteryl ester transfer protein activity. Results: Multiple regression showed that only BBIT (but neither limitation of weight gain nor metformin) reduced maternal TG z ‐scores ( P  = 0.011). When the 131 pregnancies were split into two groups – without BBIT ( n  = 58; HbA1c = 5.3 ± 0.3%) and with BBIT ( n  = 73; HbA1c = 5.4 ± 0.6; P  = 0.2005) – we observed that BBIT ( n  = 73) reduced maternal TG z ‐scores in a dose‐related fashion (Jonckheere–Terpstra P  = 0.03817). The atherogenic index of plasma remained within normal range in both groups. Conclusion: BBIT (but not weight gain control nor metformin) reduced maternal TG in mothers with glucose‐controlled GDM. This beneficial effect of BBIT was not related to changes in the cholesteryl ester transfer protein activity.